Dictyochophyceae Plastid Genomes Reveal Unusual Variability in Their Organization. Issue 5 (27th August 2019) - Han, Kwi Young; Maciszewski, Kacper; Graf, Louis; Yang, Ji Hyun; Andersen, Robert A.; Karnkowska, Anna; Yoon, Hwan Su
Abstract : Dictyochophyceae (silicoflagellates) are unicellular freshwater and marine algae (Heterokontophyta, stramenopiles). Despite their abundance in global oceans and potential ecological significance, discovered in recent years, neither nuclear nor organellar genomes of representatives of this group were sequenced until now. Here, we present the first complete plastid genome sequences of Dictyochophyceae, obtained from four species: Dictyocha speculum, Rhizochromulina marina, Florenciella parvula and Pseudopedinella elastica . Despite their comparable size and genetic content, these four plastid genomes exhibit variability in their organization: plastid genomes of F. parvula and P. elastica possess conventional quadripartite structure with a pair of inverted repeats, R. marina instead possesses two direct repeats with the same orientation and D. speculum possesses no repeats at all. We also observed a number of unusual traits in the plastid genome of D. speculum, including expansion of the intergenic regions, presence of an intron in the otherwise non‐intron‐bearing psa A gene, and an additional copy of the large subunit of RuBisCO gene ( rbc L), the last of which has never been observed in any plastid genome. We conclude that despite noticeable gene content similarities between the plastid genomes of Dictyochophyceae and their relatives (pelagophytes, diatoms), the number of distinctive features observed in this lineage strongly suggests that additional taxa require further investigation.